2022
DOI: 10.5430/jct.v11n5p64
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress and Academic Staff Job Performance in Two Nigerian Universities

Abstract: Available reports provide an account of academic staff’s poor job performance in higher education institutions and universities in particular. Consequently, a growing body of research has been attracted to this area, including those seeking ways to understand the problem and others aimed at proffering solutions. This study contributes to the literature by investigating the influence of occupational stress on the job performance of academic staff in universities. Three null hypotheses directed the study in line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…This study found that the average impact of occupational stress on the mental health of lecturers from the departments of interest was mild. Consistent with the result of this study, Akah et al (15) , reported that stress occurrence among university academic staff or other workers is a pervasive trend in almost all nations worldwide. More so, with the development of society and continuous advancement in science and technology, the work requirements for professional people are constantly improving, and the detection rate of occupational stress also increases.…”
Section: Discussionsupporting
confidence: 92%
“…This study found that the average impact of occupational stress on the mental health of lecturers from the departments of interest was mild. Consistent with the result of this study, Akah et al (15) , reported that stress occurrence among university academic staff or other workers is a pervasive trend in almost all nations worldwide. More so, with the development of society and continuous advancement in science and technology, the work requirements for professional people are constantly improving, and the detection rate of occupational stress also increases.…”
Section: Discussionsupporting
confidence: 92%
“…This result corroborates other previous studies which have documented an unfavourable effect of excessive alcohol consumption on consumers' mood (Alford et al, 2020), workplace productivity (Łyszczarz, 2019;Stepanek et al, 2019) and presenteeism (Buvik et al, 2018;Lee et al, 2021). Past studies on stress have also documented its negative effect on job performance (Aduma et al, 2022;Akah, Owan, Aduma, et al, 2022;Daniel, 2019) and other work-related variables such as productivity (Ma & Ye, 2019;Ramos-Galarza & Acosta-Rodas, 2019) and job satisfaction (An et al, 2020;O'Brien et al, 2019).…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…Past studies on mental stress have also documented its negative effect on the job performance of academic staff (Aduma et al, 2022;Akah, Owan, Aduma, et al, 2022;Daniel, 2019) and other work-related variables such as productivity (Ma & Ye, 2019;Ramos-Galarza & Acosta-Rodas, 2019) and job satisfaction (An et al, 2020;O'Brien et al, 2019). This means that the more academic staff are exposed to stressful conditions, the higher the declining chances of their job performance, other things being equal.…”
Section: Mental Stressmentioning
confidence: 99%
“…In the opinion of Dada, Okpara, Adeleke, Okon, Merimekwu, Anagbogbu, Petters, Edu, Eno, Akah and Olofu (2022), the management strategies for higher education in the 21st century vary from organization to organization but to some extent share some similarities. Therefore, this work has identified and explicated eleven management strategies that can be utilized by higher education administrators.…”
Section: Types Of Management Strategies For Higher Education Administ...mentioning
confidence: 99%